The Heroes Crossing the Line: An Evaluation of Making Enemies in Turkic Epics/ Çizgiyi Aşan Kahramanlar: Türk Destanlarında Düşman Yaratma Eylemi Üzerine Bir Değerlendirme - Mustafa Duman (Folklor/Edebiyat, 2020)
This study investigates the origins of making an enemy through examples taken from Turkic epics, and offered personal evaluations on the relationship between epics and real world politics. In order to make a comprehensive evaluation, 30 epic texts selected from different regions of the Turkic world constitute the scope of this study. The similar features of the enemy in these epics were determined through a structuralist analysis. However, the epics included in the present study are merely some containing typical examples of enemy-making: the epic of Oguz Kagan, the epic of Koroghlu (Anatolian version), Manas and Kocacas epics of Kyrgyz, the epic of Koblan Batir of Bashkirs and the Book of Dede Korkut. By analyzing the epics from different perspectives, the aim was to put forward a classification of the enemies in the epic stories. It was also aimed to contribute to the knowledge of better understanding of the causes of the conflict and the relationship between politics and epics as well as their influences upon one another.